(untitled) (Research, Society and Development, 2023)
Odontogenic cysts belong to a group of lesions of the jaws, which are relatively common in the oral cavity, mainly involving the maxilla. Studies demonstrate the wide variety of cysts and their individualized treatments aimed at better monitoring of the patient involved. This paper aims to carry out a clinical case report of the treatment of an Orthokeratinized Odontogenic Cyst (OKC) in an adult, female, 26 years old, black, admitted to the Getúlio Vargas University Hospital (HUGV), asymptomatic. Upon clinical examination, requested routine panoramic radiograph, the presence of an unilocular lesion with well-delimited borders in the right hemi-maxilla was noted, close to dental element 17, suggestive of an odontogenic cyst. The approach proposed in the case cited was surgical treatment of the lesion carrying out total enucleation and curettage for the purpose of subsequent referral to the department of Pathology at the State University of Amazonas (UEA) for histopathological analysis. Macroscopically, the lesion had an irregular, elastic, brownish surface measuring approximately 2.5 x 3.0 x 1.0 cm. Microscopic sections reveal a cystic cavity coated with orthokeratin and serous exudate with cholesterol crystals, confirming the diagnosis of Orthokeratinized Odontogenic Cyst. The treatment performed proved to be successful, not showing remission sinals til the present moment and shows the importance of histopathological differentiation for the proservation of the case, since the morphological richness of the transition of lining epithelia indicates the often necessary follow-up of the patient, who, in six months of follow-up, is if without any sequelae or lesion recurrence.